2009
DOI: 10.1128/ec.00091-09
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations in the Glucose Metabolism of Procyclic Trypanosoma brucei Isolates from Tsetse Flies and during Differentiation of Bloodstream Forms

Abstract: Procyclic forms of Trypanosoma brucei isolated from the midguts of infected tsetse flies, or freshly transformed from a strain that is close to field isolates, do not use a complete Krebs cycle. Furthermore, short stumpy bloodstream forms produce acetate and are apparently metabolically preadapted to adequate functioning in the tsetse fly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 25 publications
4
27
0
Order By: Relevance
“…L. passim was initially cultured under normoxia and migrated into the anaerobic honey bee hindgut, causing it to down-regulate the genes involved in the kinetoplast respiratory chain during middle to late stages of the infection (PI 12-27). Similar shifts in energy metabolism are also observed in other trypanosomatid parasites [41][42][43][44] . The parasites actively swim in the cultured medium using the flagellum and ATP; however, the loss of flagellum (see below) makes them immobile in the honey bee hindgut.…”
Section: Discussionsupporting
confidence: 75%
“…L. passim was initially cultured under normoxia and migrated into the anaerobic honey bee hindgut, causing it to down-regulate the genes involved in the kinetoplast respiratory chain during middle to late stages of the infection (PI 12-27). Similar shifts in energy metabolism are also observed in other trypanosomatid parasites [41][42][43][44] . The parasites actively swim in the cultured medium using the flagellum and ATP; however, the loss of flagellum (see below) makes them immobile in the honey bee hindgut.…”
Section: Discussionsupporting
confidence: 75%
“…However, these genes appear to be down-regulated at later infection stages as the parasite switches to a dormant stage without active metabolism and proliferation. Similar shifts in energy metabolism are also observed in other trypanosomatid parasites (Bringaud et al 2006, Smith et al 2017, Van Grinsven et al 2009, van Hellemond et al 2005). Furthermore, the continuous down-regulation of tryparedoxin 1, tryparedoxin-like , and tryparedoxin peroxidase genes throughout the infection cycle is also consistent with the reduced production of radical oxygen species in anaerobic environments.…”
Section: Discussionsupporting
confidence: 77%
“…The bloodstream forms of T. brucei depend entirely on glucose metabolism through glycolysis, whose enzymes are compartmentalized in glycosomes and in turn have repressed mitochondrial activities ( 66 ). In contrast, insect forms, which need to survive in different regions of the tsetse fly’s digestive system wherein the glucose supply is irregular, rely on mitochondrial metabolism for ATP production and have sparse glycosomes ( 67 ). It has been recently shown that bloodstream forms overexpressing ATG8 proteins and incubated in a differentiation medium have a delayed transition to insect forms, as illustrated by a longer retention of glycosomes ( 68 ).…”
Section: Discussionmentioning
confidence: 99%